Effects of Laparoscopic Hartmann Reversal on Short-term Operative Outcomes Among Vietnamese Patients - Ung,Viet Van (2021)
Abstract Background The reestablishment of continuity after Hartmann operation is considered a major surgical procedure with high morbidity and mortality. The optimal interval time between the Hartman procedure and reversal is controversial. Our study aimed to evaluate the effectiveness of laparoscopic Hartmann reversal and to determine the optimal timing of operation. Methods All patients who underwent laparoscopic Hartmann reversal from 2008 to 2019 (11 years) at the University Medical Center (UMC) in Ho Chi Minh City were recruited and divided into 2 groups according to the interval time (≤ 4 or>4months). The short-term operative outcomes of these groups were compared. Results There were 66 patients who underwent laparoscopic Hartmann reversal (mean age: 63.2 years old); ~ 77% of them had colorectal cancer, and 17% had complicated diverticular disease. Themortality rate, anastomotic leakage rate, and overall complication rate were 0%, 1.5%, and 13.2%, respectively. Early operation was performed in 36 patients, and late reversal in 28 patients. There was no difference in mortality, anastomotic leakage, operative complications, and hospital stay between the two groups. Conclusion Laparoscopic Hartmann reversal was effective with acceptable morbidity and mortality at the UMC. There was no observed impact of the interval time between the Hartmann procedure and laparoscopic Hartmann reversal on the short-term operative outcomes.